The design and testing of a power augmented wind turbine system for urban high rise application / Pan Kok Chen - Pan, Kok Chen (2012)
The utilization of renewable energy such as wind energy and solar energy is receiving great attention due to the elevated price of fossil fuels in the international market as well as adverse environmental problems from the process of power generation. On-site generation is becoming more widespread for dwelling places, for example, photovoltaic panels, micro- CHP (Combined Heat and Power) and micro-wind. For on-site generation, building integrated wind turbines and solar energy systems serve as attractive opportunities. Retrofitting high-rise building would be a feasible choice for on-site wind turbine integration since no huge capital investment is involved. However, urban areas generally have weak and turbulent wind conditions due to the presence of high rise buildings. On the other hand, concerns such as visual impact, acoustic pollution, structural issues, safety problems, blade failures and electromagnetic interference need to be addressed. The wind energy generation systems for urban regions on-site generation need to overcome these disadvantages. In this study; an innovative, omni-directional-guide-vane (ODGV) which enhances the performance of a VAWT (vertical axis wind turbine) is introduced. The shrouded design of the ODGV can minimize the public concerns of installing a high-speed rotating wind turbine for on-site power generation and it is aesthetically friendly to an existing building. Through wind tunnel experiment, the ODGV capable to improve the power output of a model drag type VAWT (height = 250 mm, diameter = 500 mm) for 51%, 40%, 30%, and 25% at wind speed 3 m/s, 4.5 m/s, 6.0 m/s and 7.5 m/s respectively. An extended CFD (Computational Fluid Dynamics) study of the ODGV on lift type VAWT has shown encouraging results. The CFD study was to compare the effect of the ODGV on the lift type VAWT by re-simulating the experiment of a single bladed (NACA 0015 airfoil) VAWT published by the Sandia Lab. The simulation boundary conditions are identical to the Sandia Lab experimental conditions at tip speed ratio, TSR=2.5 and TSR=5. The turbulence model used is shear stress transport (SST) k-ω. From the simulated results, with the employment of the ODGV, it is shown that the torque output of the NACA 0015-airfoil, single bladed VAWT has been increased by 57% and 35% at TSR=2.5 and TSR=5 respectively. As a conclusion, the ODGV wind power generation system improves the power output performance of a VAWT (both drag type and lift type) and it has great potential to be sited in urban areas for on-site and grid-connected power generation.